The Effect of Waste Marble Dust and Corncob Ash on the Engineering and Micro-Structural Properties of Expansive Soil for Use in Road Subgrades - Wongbae, Leonardo Z.; Kabubo, Charles; Owayo, Alphonce (Engineering, Technology & Applied Science Research, 2024)
This research investigated the effect of Waste Marble Dust (WMD) and Corncob Ash (CCA) on expansive soil’s engineering and microstructural properties. Various laboratory experiments were performed on the natural soil to ascertain its characteristics. The corncobs underwent pre-water treatment for fourteen days to remove excess potassium and increase their silica content, resulting in a rise in the silica level from 0% to 50%. At first, only WMD was added to the soil in increments of 5% to 30% using compaction and California bearing tests. The optimum dosage of 15% WMD addition yielded the best result. CCA was then incorporated by the weight of the soil from 2% to 10% in increments of 2% to the first optimum (15% WMD) to obtain the overall optimum for the study (15% WMD and 8% CCA). Stabilization of the natural soil using both materials led to the modification and solidification of the soil mass, evident by the rise in California bearing ratio values from 1.68% to 15.53% and unconfined compressive strength from 41.33 kN/m2 to 174.68 kN/m2. There was also a decrease in the soil’s free swell from 120% to 15% as well as reductions in the liquid limits from 56.23% to 36.01% and in the plasticity index from 29.74% to 8.72%, respectively. The microstructural images showed the formation of cementitious compounds in the form of calcium silicate hydrate and calcium aluminate hydrate gels. The findings indicate that using WMD and CCA as a unit has great potential in enhancing engineering properties, like strength parameters and the swell potential of expansive soils.